2015
DOI: 10.1152/ajpheart.00854.2014
|View full text |Cite
|
Sign up to set email alerts
|

ACE2/Ang-(1–7)/Mas axis stimulates vascular repair-relevant functions of CD34+cells

Abstract: CD34(+) stem/progenitor cells have been identified as a promising cell population for the autologous cell-based therapies in patients with cardiovascular disease. The counter-regulatory axes of renin angiotensin system, angiotensin converting enzyme (ACE)/Ang II/angiotensin type 1 (AT1) receptor and ACE2/Ang-(1-7)/Mas receptor, play an important role in the cardiovascular repair. This study evaluated the expression and vascular repair-relevant functions of these two pathways in human CD34(+) cells. CD34(+) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…4 C ). In agreement with this and our previous studies in human CD34 + cells (19), SDF- or VEGF-induced migration of LSK cells in vitro was attenuated by Y-27632, a ROCK inhibitor ( P < 0.05, vs. SDF) (Fig. 4 E ).…”
Section: Resultssupporting
confidence: 92%
“…4 C ). In agreement with this and our previous studies in human CD34 + cells (19), SDF- or VEGF-induced migration of LSK cells in vitro was attenuated by Y-27632, a ROCK inhibitor ( P < 0.05, vs. SDF) (Fig. 4 E ).…”
Section: Resultssupporting
confidence: 92%
“…Recent studies showed that local RAS modulate hematopoietic and cardiovascular reparative functions of BMSPCs (Rodgers and diZerega, 2013). We and others have shown evidence for the expression of mRNA and protein of ACE or ACE2 in human and mouse BMSPCs (Abali et al, 2002; Oliveira et al, 2010; Thatcher et al, 2011; Jarajapu et al, 2013; Singh et al, 2015). …”
Section: Introductionmentioning
confidence: 78%
“…XNT adminstration also prevented the increase in right ventricular systolic pressure and hypertrophy in a monocrotaline-induced pulmonary hypertension model (169) and attenuated thrombus formation in SHR (190). Numerous protective effects have been reported with diminazene aceturate (DIZE), another putative ACE2 activator (102,118,119,184,186,335,341,357,429,445,511,513,535,566). It should be pointed out, however, that the beneficial effects of these small-molecule activators might also depend on ACE2-independent mechanisms (234).…”
Section: Pharmacological Toolsmentioning
confidence: 99%